Bibliometric analysis of global sediment research: publication trends and development directions in sedimentology - Циганенко-Дзюбенко, І.Ю.; Кірейцева, Г.В.; Хамдош, І.Н.; Вовк, В.М. (Київський національний університет імені Тараса Шевченка, 2025)
A comprehensive bibliometric analysis of global sediment research for the period 2020-2024 was conducted based on 3,457 scientific publications from the Scopus database using VOSviewer software package for scientific network visualization and cluster analysis. The study encompassed systematization of publications by key terms “sediment*”, “bottom deposit*”, “lacustrine sediment*”, “marine sediment*”, “river sediment*” with subsequent terminology standardization and relevance verification. Cluster analysis revealed five main thematic groups of modern sedimentology: pollution and toxicity assessment (green cluster), ecosystem processes and biodiversity (red cluster), marine and coastal research (blue cluster), biogeochemical cycles (yellow cluster), and methodological approaches (purple cluster). Advanced data preprocessing protocols ensured temporal consistency and spatial correlation analysis across research domains. The analysis incorporated co-occurrence mapping of keywords, co-citation analysis of influential works, and bibliographic coupling to identify research collaboration patterns. Network visualization parameters were optimized with minimum term occurrence threshold of 5, association strength normalization, and Leiden clustering algorithm with resolution parameter 1.0 for optimal cluster delineation. Geographic analysis demonstrated dominance of USA (1,000 publications, 29%) and China (450 publications, 13%) in global research structure. Thematic classification revealed transformation of sedimentology from geological discipline to integrated environmental science with Environmental Science dominance (39.8% of publications). Temporal dynamics characterized by U-shaped curve with minimum in 2022 (630 publications) and recovery to 706 publications in 2024. Current research directions include heavy metal studies (25-30% of publications), microplastics research (15-20%), and environmental monitoring (20-25%). Emerging development areas encompass artificial intelligence applications, nanopollutant research, microbiome studies, and digital twins of aquatic ecosystems, demonstrating revolutionary potential for transforming methodological approaches and practical applications of sedimentology in sustainable water resource management context. The study provides evidence-based framework for strategic research planning and international collaboration optimization in critical environmental science domains.

Проведено комплексний бібліометричний аналіз світових досліджень донних відкладів за період 2020-2024 рр. на основі бази даних Scopus. Досліджено публікаційну активність 3457 наукових робіт, що охоплюють різні аспекти седиментології. Виявлено домінування США (1000 публікацій) та Китаю (450 публікацій) у глобальній структурі досліджень. Встановлено, що Environmental Science становить 39,8% всіх публікацій, демонструючи трансформацію седиментології від геологічної дисципліни до інтегрованої науки про довкілля. Кластерний аналіз ключових термінів за допомогою VOSviewer виявив п’ять основних тематичних груп: забруднення та токсичність, екосистемні процеси, морські дослідження, біогеохімічні цикли та методологічні підходи. Зафіксовано тимчасове зниження публікаційної активності у 2022 році (630 публікацій) з подальшим відновленням до 706 публікацій у 2024 році. Ідентифіковано актуальні напрямки досліджень: забруднення важкими металами (25-30% публікацій), мікропластик (15-20%), екологічний моніторинг (20-25%). Визначено перспективні галузі розвитку: застосування штучного інтелекту, дослідження нанозабруднювачів, мікробіомні дослідження та цифрові двійники водних екосистем.
Бібліометричний аналіз світових досліджень донних відкладів: тенденції публікацій та напрями розвитку седиментології
Keywords: бібліометричний аналіз; донні відклади; седиментологія; VOSviewer; публікаційна активність; забруднення водних екосистем; мікропластик; важкі метали; екологічний моніторинг; bibliometric analysis; sediments; sedimentology; publication activity; aquatic ecosystem pollution; microplastics; heavy metals; environmental monitoring